Analysis of Domestic Resources in Robusta Coffee Farming in Pasuruan Regency Using the Domestic Resource Cost (DRC) Approach - Putri Nikita Brenadevari; Gyska Indah Harya; Sri Widayanti (Danadyaksa: Post Modern Economy Journal, 2026)
Coffee is one of the strategic agricultural commodities that plays a vital role in the Indonesian economy, serving as a source of foreign exchange, a provider of employment, and a source of income for farmers. Pasuruan Regency is one of the major centers for Robusta coffee production in East Java Province and holds significant potential for further development. However, improving the competitiveness of Robusta coffee depends not only on product quality but also on the efficiency of domestic resource use in the production process. This study aims to analyze the efficiency of domestic resource use in Robusta coffee farming in Pasuruan Regency using the Domestic Resource Cost (DRC) approach. The study was conducted in Puspo and Tutur subdistricts, Pasuruan Regency, using purposive sampling. The data used included primary data obtained through interviews and questionnaires administered to Robusta coffee farmers, as well as secondary data from the Central Statistics Agency, the Directorate General of Plantations, and relevant literature. Data analysis utilized the Policy Analysis Matrix (PAM) method, focusing on the Domestic Resource Cost (DRC) indicator. The study results indicate that the DRC value for robusta coffee farming in Pasuruan Regency is 0.050. This value indicates that robusta coffee farming possesses a comparative advantage because the DRC value is < 1, meaning the use of domestic resources is economically efficient. Thus, Robusta coffee in Pasuruan Regency has the potential to be further developed as a leading regional commodity capable of competing in both domestic and international markets.